Identification of QTL for Tolerance to Flooding Stress at Seedling Stage of Soybean (Glycine max L. Merr.) - Sanjeev Kumar Dhungana; Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Sang-Ouk Shin; Jae-Hyeon Oh; In-Youl Baek (Agronomy, 2021)
Flooding stress is a serious problem in soybean production, causing a remarkable yield reduction. The onset of rainy season during the early growth of soybean in Korea and some other parts of the world potentially subjects soybean plants to flooding stress. The objective of this study was to map quantitative trait loci (QTL) for flooding tolerance using a recombinant inbred line (RIL) population derived from a cross between ‘Danbaekkong’ (flood-tolerant) and ‘NTS1116′ (flood-susceptible) cultivars grown in a plastic house for two years. The plants were flood-stressed at the V1-V2 stage by ponding about 10 cm water from the soil surface. Leaf chlorophyll content and shoot dry weight were measured under control and flooded conditions to map the QTL. The genetic map was constructed using 1689 polymorphic markers obtained from the 180K Axiom® SoyaSNP markers used for genotyping the population. Ten QTL with 3.39–5.14 logarithm of odds scores and 8.1–30.7% phenotypic variations (PVE) were identified on seven chromosomes. One QTL on chromosomes 6 and 15 and two QTL on chromosome 7 were detected at least in two different environments causing up to 30.7% PVE, suggesting their potential applications in the breeding of flood-tolerant soybeans. The results could be useful in further exploring the genetic basis of flooding tolerance and developing tolerant cultivars of soybean.